Applications of Convolutional Neural Networks in vehicle damage recognition - Brito, Erick Roberto Furst (Seven Editora, 2024)
Convolutional Neural Networks (CNNs) have demonstrated exceptional performance in a variety of computer vision tasks. This article explores the use of CNNs in the context of vehicle damage recognition, with a focus on the integration of a product called IVI (Intelligent Vehicle Inspection) developed for this purpose. DOI:https://doi.org/10.56238/sevened2023.006-146